Effect of stocking density on growth and survival of Nile tilapia (Oreochromis niloticus, Linnaeus 1758) under cage culture in Lake Albert, Uganda - Abaho, Ivan; Zaabwe, Thaddeus; Izaara, Andrew; Kasigwa, Howard N.; Mushabe, Norman; Byenkya, Steven; Nkambo, Mujibu; Baguma, Sylvester D.; Hafashimana, David L. N.; Efitre, Jackson (International Journal of Fisheries and Aquaculture, 2020)
In Uganda fish is a great source of animal dietary protein, however, natural stocks continue to decline. Therefore, aquaculture provides a viable option to bridge the increasing fish supply-demand gap. Accordingly, a study was conducted from March to August 2016 to investigate the effect of stocking density on the growth performance, and survival of Nile tilapia (Oreochromis niloticus) in floating netcages to contribute to aquaculture production in Uganda. Nile tilapia fingerlings, with an average weight of 4.07 g were stocked in 8 m3 cages at three different stocking densities; 200, 250, and 300 fish/m3, and fed on a locally formulated commercial feed for 180 days. At the end of the experimental period, results showed that fish stocked at lower densities were heavier than those stocked at higher densities. The mean final weights of fish were; 150.79±85.71, 127.82±68.43 and 118.73±49.29 g in cages stocked with 200, 250 and 300 fish/m3, respectively. The mean final weight in lower density (200 fish /m3) treatments was significantly higher (P<0.05) than that of higher density (300 fish/m3) treatments. The mean relative condition factor of fish ranged from 1.02 to 1.06, but was not significantly different (P>0.05) among the stocking densities. Survival rate and stocking density were negatively correlated. The best survival rate (94.19%) was obtained in low stocked cages (200 fish/m3) compared to 92.98% in highly stocked cages (300 fish/m3). The results of this study suggest that 200 fish/m3 of a cage, is the best stocking density in terms of fish growth parameters.
Keywords: Aquaculture; Animal protein; per capita; Livelihood; Yield